VARIOUS METHODS OF TEACHING FRENCH - Muxayyo Gulamamatovna, Rixazanova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to examine contemporary methods for teaching French as a foreign language, focusing on identifying effective strategies that enhance learner engagement and linguistic proficiency. Method: A qualitative approach was utilized, involving classroom observations and theoretical analysis in educational institutions across Samarkand, Uzbekistan. The study evaluated methods such as imitation-based learning, discussion-oriented activities, experiential learning, and professional simulations. Results: The findings reveal that imitation significantly supports young learners in mastering pronunciation, vocabulary, and intuitive language patterns. Experiential learning, including internships and real-world interactions, fosters communicative competence and learner confidence. Furthermore, discussion-based techniques enhance critical thinking, active participation, and analytical skills. Novelty: This research contributes to the field by providing an integrative analysis of underexplored pedagogical practices within the Central Asian context, advocating for a learner-centered, flexible, and contextually relevant approach to French language instruction.